2015
DOI: 10.1007/s12040-015-0588-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geomagnetic storm on low latitude ionospheric total electron content: A case study from Indian sector

Abstract: The effect of geomagnetic storms on low latitude ionosphere has been investigated with the help of Global Positioning System Total Electron Content (GPS-TEC) data. The investigation has been done with the aid of TEC data from the Indian equatorial region, Port Blair (PBR) and equatorial ionization anomaly region, Agartala (AGR). During the geomagnetic storms on 24th April and 15th July 2012, significant enhancement up to 150% and depression up to 72% in VTEC is observed in comparison to the normal day variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…2 and 3) and shifting of the crests in the direction of the poles observed in Fig. 4, as previously mentioned and suggested by many studies (e.g., Tsurutani et al, 2004;Mannucci et al, 2005;Astafyeva, 2009;Astafyeva et al, 2014;Chakraborty et al, 2015), the mechanism at work is the ionospheric super-fountain effect. Finally, it is also worth mentioning that this would be the second time a LTE has been detected since 2016, as the first one was the one observed during the 20 April 2018 geomagnetic storm (Sotomayor-Beltran, 2018).…”
Section: Creation Of 8 September 2017 Ltesupporting
confidence: 81%
See 1 more Smart Citation
“…2 and 3) and shifting of the crests in the direction of the poles observed in Fig. 4, as previously mentioned and suggested by many studies (e.g., Tsurutani et al, 2004;Mannucci et al, 2005;Astafyeva, 2009;Astafyeva et al, 2014;Chakraborty et al, 2015), the mechanism at work is the ionospheric super-fountain effect. Finally, it is also worth mentioning that this would be the second time a LTE has been detected since 2016, as the first one was the one observed during the 20 April 2018 geomagnetic storm (Sotomayor-Beltran, 2018).…”
Section: Creation Of 8 September 2017 Ltesupporting
confidence: 81%
“…A recent study by Lei et al (2018), using diverse instruments (e.g., satellites and ionosondes), has also observed this TEC enhancement in the Asian-Australian region for this geomagnetic storm. The increment of VTEC in the EIA was already observed in previous studies about ionospheric responses to geomag- netic storms (e.g., Zhao et al, 2005;Pedatella et al, 2009;Astafyeva et al, 2015;Chakraborty et al, 2015).…”
Section: Gim Mapssupporting
confidence: 74%
“…Furthermore, the equatorial latitude station Nazret, NAZR (8.57 ∘ N, 39.29 ∘ E; 0.25 ∘ S, geomagnetic) was also considered to study ionospheric response. The ionospheric storm effects observed from the low-latitude regions can be explained by electrodynamic effects (PPEF and DDEF) and mechanical effects (such as thermospheric composition changes and storm-induced equatorward neutral wind effect) (Buonsanto, 1999;Chakraborty et al, 2015;Mendillo, 2006;Prölss, 1995). Figure 8 shows the ionospheric storm effects distributions for low and equatorial latitude stations, MBAR, SHEB, and NAZR, which are located within EIA.…”
Section: Low and Equatorial Ionospheric Responsementioning
confidence: 99%
“…Shagimuratov et al (2002) reported large and medium level irregularities in TEC variations over high-latitude regions of ionosphere during storm time. Chackraborty et al (2015) investigated the impact of geomagnetic activities on TEC and observed TEC variations significantly, especially in the equatorial region and EIA region, during the geomagnetic storms. The ionospheric effects to the strongest geomagnetic storm have resulted in complex effects around the Earth (Astafyeva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%